THE ROLE OF FIQH AL-SIYAR IN INTERNATIONAL LAW-MAKING Escaping the Lethargy - Muhammadin, Fajri Matahati; Azzahra, Shania Dwini (2022)
International law has developed since its pre-20th century consent-based positivistic framework to ‘international law-making’ where the role of state sovereignty is seen to have eroded. This development, however, still reproduces its pre-20th century colonialist features against non-European (including Islamic) legal thought, pushing them to the peripheries of relevance. Recently, countering that, stronger voices have demanded international law to generally include non-European and specifically Islamic international legal scholarship. However, while having a very rich body of classical scholarship, contemporary literature of fiqh al-siyar (Islamic international law) suffers from lethargy. It neither mentions nor responds to the trend of international law-making. This article, employing a literature-based research approach, bridges the gap of that lethargy so that fiqh al-siyar could develop to properly respond to the current trend of international law-making. It is found that fiqh al-siyar must critically adopt and respond to the features of international law-making, and all actors must utilize all channels to participate in its process © 2022, Al-Jami'ah.All Rights Reserved.